Perinatal Mental Health in Women with Polycystic Ovary Syndrome: A Cross-Sectional Analysis of an Australian Population-Based Cohort - Tay, Chau Thien (J Clin Med, 2019)
Women with polycystic ovary syndrome (PCOS) have many risk factors associated with perinatal mental disorders, but research in this area is scarce. This study aims to compare the prevalence of common perinatal mental disorders in women with and without PCOS, and examine the relationship between PCOS and common perinatal mental disorders. We performed a cross-sectional study on self-reported data of 5239 women born between 1973 to 1978 in the Australian Longitudinal Study on Women’s Health. Compared with women not reporting PCOS, women reporting PCOS had higher prevalence of antenatal depression (8.9% vs. 4.4%, p < 0.001), antenatal anxiety (11.7% vs. 5.6%, p < 0.001), postnatal depression (26.8% vs. 18.6%, p < 0.001) and postnatal anxiety (18.4% vs. 12.0%, p < 0.001). PCOS was positively associated with antenatal depression and/or anxiety (adjusted odds ratio 1.8, 95% confidence interval 1.2–2.6) but not postnatal depression and/or anxiety after controlling for sociodemographic and lifestyle factors, reproductive history, obstetric complications and pre-existing depression and anxiety. General perinatal guidelines currently do not recognize PCOS as a risk factor and the international evidence based PCOS guideline noted inadequate evidence in this area. This paper addresses the gap in literature and highlights the need to screen for common perinatal mental disorders in women with PCOS.